Leading in Team Fragmentation: Examining Leadership Strategies in Multi-Sector Organizations Structures in Indonesia - Ida Ayu Dwi Purnami; Putu Irma Yunita; Luh Putu Mahyuni (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Team fragmentation in multitasking organizations challenges coordination and communication. This study aims to analyze leadership strategies for addressing team fragmentation in multitasking organizations in Indonesia, particularly in the logistics, manufacturing, and medical technology sectors. This study employed a qualitative multiple-case study using interviews, observations, and documentation to examine adaptive leadership, distributed leadership, and organizational development practices. The results indicate that adaptive leadership plays a crucial role in creating a sense of psychological safety, communicating change clearly, maintaining emotional stability, and strengthening team connectedness. Role distribution patterns in multitasking teams are flexible, collective, and contextual, according to the sector’s characteristics. In logistics, role distribution is supported by cross-functional coordination, formal documentation, shared Key Performance Indicators (KPIs), and regular meetings. Manufacturing relies on cross-unit collaboration, Standard Operating Procedures (SOPs), briefings, and target monitoring, while medical technology adopts project-based collaboration across specialties supported by training, project reviews, and feedback mechanisms. Organizational development principles are applied through development interventions, organizational evaluations, changes in intentions, and improvements to coordination mechanisms. This study extends Adaptive Leadership Theory by demonstrating that adaptive leadership and distributed leadership operate as complementary mechanisms rather than independent leadership approaches in fragmented multitasking organizations.